2022
DOI: 10.3390/jcm11195840
|View full text |Cite
|
Sign up to set email alerts
|

Two Year Functional and Structural Changes—A Comparison between Trabeculectomy and XEN Microstent Implantation Using Spectral Domain Optical Coherence Tomography

Abstract: The aim of this study was to analyze retinal nerve fiber layer (RNFL) thickness after trabeculectomy (TE) versus XEN microstent implantation (XEN) in primary open-angle glaucoma (POAG) cases naïve to prior incisional glaucoma surgery. We examined 119 consecutive glaucoma patients retrospectively, who received a TE or XEN for medically uncontrolled POAG. Intraocular pressure (IOP), amount of IOP-lowering medication, mean deviation of standard automated perimetry and peripapillary RNFL thickness were evaluated d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…These developments are comparable to the results observed in our TE group. However, we added further descriptions of functional (visual field test) and anatomical (RNFL thickness) development after surgery, adding to the already published knowledge about the effectiveness of TE [ 11 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These developments are comparable to the results observed in our TE group. However, we added further descriptions of functional (visual field test) and anatomical (RNFL thickness) development after surgery, adding to the already published knowledge about the effectiveness of TE [ 11 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, limited data exist concerning the long-term structural and functional outcomes after TE and DS. However, it has been shown before that after surgical glaucoma intervention, further RGC loss develops although sufficient IOP decrease [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that RGC loss continues after glaucoma surgery. In another study of POAG eyes that underwent TE or XEN microstent implantation, we already demonstrated that although the preoperative target IOP levels were achieved, the peripapillary RNFL thickness continued to decrease during the first year after surgery and remained stable during the second year after surgery [ 38 ]. This further RNFL loss occurred without evidence of further functional deterioration and was more pronounced in the TE group than in the XEN implantation group.…”
Section: Discussionmentioning
confidence: 99%